Strengthening the Muslim Community in Indonesia and Beyond: The 2013 Islamic Solidarity Games in Palembang - Friederike Trotier (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2015)
The city of Palembang hosted the third Islamic Solidarity Games (ISG) in September/October 2013 and welcomed 39 nations to this sporting event. In particular, I seek to address the question of to what extent the ISG served as a tool to unite Muslims of Indonesia, especially of Palembang, and Muslims from participating countries. The motto of the games, “Unity in Harmony”, conveyed a strong desire to strengthen the Muslim community and identity in Indonesia and worldwide. However, several issues indicate a discrepancy between ideal of the motto and the reality of the games in Indonesia. The perceived exclusion of other religious groups and the discussion about the “appropriate” clothing of female athletes were among some of the sticking points during the ISG. Furthermore, the unbridled nationalism which was exhibited by local spectators whenever Indonesia faced Malaysia hints to tensions between Muslim communities of different nations.DOI: 10.15408/sdi.v22i1.1388